2017
DOI: 10.1109/tvcg.2016.2598498
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of a Dynamic Physical Bar Chart for Data Exploration and Presentation

Abstract: Physical data representations, or data physicalizations, are a promising new medium to represent and communicate data. Previous work mostly studied passive physicalizations which require humans to perform all interactions manually. Dynamic shape-changing displays address this limitation and facilitate data exploration tasks such as sorting, navigating in data sets which exceed the fixed size of a given physical display, or preparing "views" to communicate insights about data. However, it is currently unclear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 29 publications
1
69
0
Order By: Relevance
“…Shape-changing interfaces encode and communicate information to their users through combinations of visual, haptic (tactile and/or kinaesthetic), and shape animation (transitions between states). A key example of this communication is the new field of data physicalization [47] that extends information visualization into the physical space; for example, by allowing users to physically manipulate a data-set using a dynamic bar chart [95,96]. This physicalization allows end-users to exploit their lifelong training in visual and haptic perception.…”
Section: Communicate Informationmentioning
confidence: 99%
“…Shape-changing interfaces encode and communicate information to their users through combinations of visual, haptic (tactile and/or kinaesthetic), and shape animation (transitions between states). A key example of this communication is the new field of data physicalization [47] that extends information visualization into the physical space; for example, by allowing users to physically manipulate a data-set using a dynamic bar chart [95,96]. This physicalization allows end-users to exploit their lifelong training in visual and haptic perception.…”
Section: Communicate Informationmentioning
confidence: 99%
“…In architecture and urban designs, physical models are wellestablished tools in the hands of designers -Hull and Willett [2017] discuss how such models allow for exploring spatial relationships and characteristics, support comparisons, provide context, and evoke emotion. Even data which we traditionally see in plots and charts can take on a physical form [Taher et al, 2015, Taher et al, 2017, Houben et al, 2016. Herman and Keefe [2018] experimented with 3D printing scalar fields on different kinds of surfaces and found that boxshaped glyphs ("boxcars") on spheroids ("potatoes") were most compelling for tangible interaction (users were more likely to pick them up and inspect closer).…”
Section: Physicalizationmentioning
confidence: 99%
“…Unlike other 'physicalisations' with fixed physical form, however, the use of a levitating particle display means the form can be dynamically changed over time. This means particles can represent information temporally as well as spatially; in the context of data presentation, a dynamic physical data representation such as this could enable new ways of exploring complex data [24,25].…”
Section: Expressive Voxelsmentioning
confidence: 99%